IMPROVING THE STUDENTS’ PROBLEM-SOLVING ABILITIES THROUGH THE DEVELOPMENT OF LEARNING MOTIVATION - Zubaidillah, Muh. Haris; Nuruddaroini, M. Ahim Sulthan; Suratno, Suratno (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aimed to explore the effect of learning motivation on students' problem-solving abilities. This research was quantitative research with an experimental method. The research design used was a within-group with a repeated measure type. The subjects were the students of State Islamic University of Antasari Banjarmasin, consisting of 138 people. The research instrument used was a test. The data were analyzed by repeated measures using the SPSS version 25 program with Tests of Within-Subjects analysis. Based on the analysis data, it showed that the Sphericity Assumed value was Sig. 0.00, which was less than 0.05. It meant that Ho was rejected and Ha was accepted. In other words, there was clear evidence that the treatment results had a significant effect on the development of problem-solving abilities during treatment. Therefore, the results indicated that one of the efforts to improve students' problem-solving skills was to develop student learning motivation. Abstrak: Tujuan penelitian ini adalah untuk mengeksplorasi pengaruh motivasi belajar terhadap kemampuan pemecahan masalah mahasiswa. Penelitian ini merupakan penelitian kuantitatif dengan metode eksperimen. Adapun desain penelitian yang digunakan adalah jenis within-group or individual design dengan tipe repeated measures. Subjek pada penelitian ini adalah mahasiswa pada perguruan tinggi Universitas Islam Negeri Antasari Banjarmasin dengan total sampel sejumlah 138 orang. Instrumen penelitian menggunakan tes. Data dianalisis dengan repeated measures dalam program SPSS versi 25 dengan analisis Tests of Within-Subjects. Berdasarkan hasil analisis, diketahui bahwa nilai Sphericity Assumed adalah sig. 0,00 lebih kecil dari 0,05, maka Ho ditolak dan Ha diterima, atau dengan kata lain terdapat bukti yang jelas bahwa hasil perlakuan berpengaruh signifikan terhadap perkembangan kemampuan pemecahan masalah selama perlakuan. Hasil penelitian menunjukkan bahwa salah satu upaya untuk meningkatkan kemampuan pemecahan masalah mahasiswa adalah dengan mengembangkan motivasi belajar mahasiswa.